Polyphosphate and Orthophosphate Content of Nitrosomonas europaea as a Function of Growth - Terry, K. R. (1970)
After inoculation of a stationary-phase culture of Nitrosomonas europaea into fresh growth solution, the cell-associated orthophosphate increased rapidly to 800 μmoles/g (wet weight), whereas the acid-insoluble long-chain polyphosphate content decreased rapidly to 22 μmoles/g. As growth proceeded, the orthophosphate content decreased rapidly to a level of 15 μmoles/g and the long-chain polyphosphate content gradually increased to 60 to 90 μmoles/g. When the pH of a culture of Nitrosomonas decreased during growth below approximately 7.4, the rate of nitrite and polyphosphate synthesis increased and the ratio of change in protein to change in nitrite decreased. When the pH of the culture was maintained above 7.6 throughout growth, polyphosphate accumulation, an increased rate of nitrite and polyphosphate synthesis, and a decreased ratio of change in protein to change in nitrite were not observed. Cells of Nitrosomonas apparently accumulated polyphosphate when adenosine triphosphate generated during the oxidation of ammonia to nitrite was not efficiently used to promote an increase in cell mass. The rapid hydrolysis of polyphosphate after the transfer of stationary-phase cells into fresh growth solution was found to be triggered primarily by the higher pH of the fresh growth solution. The efflux of orthophosphate during culture growth was not associated with a decrease in the pH of the growth solution. Data on the chemical composition of Nitrosomonas are presented.